A simple method to detect phrenic nerve impairment during cryoballoon ablation of atrial fibrillation using aVF in the standard surface ECG. (25th November 2020) - Schaerli, N; Knecht, S; Spies, F; Madaffari, A; Osswald, S; Sticherling, C; Kuehne, M
Abstract: Background: Phrenic nerve palsy (PNP) is the most common complication in cryoballoon ablation of atrial fibrillation. Monitoring techniques such as compound motor action potential (CMAP) measurements using additional leads, or catheters positioned in the subdiaphragmatic hepatic vein or the esophagus have demonstrated to be effective to prevent PNP. Purpose: This study investigates the safety and feasibility of a simple monitoring strategy using the lead aVF of the standard surface 12 lead ECG for CMAP monitoring to prevent PNP. Methods: In 263 continuous patients undergoing cryoballoon ablation, a decapolar catheter was placed in the right subclavian vein to stimulate the phrenic nerve during ablation of the right sided pulmonary veins (12V@2.9 ms at 60 bpm). Capture was continuously monitored using the CMAP potential in the inferior aVF lead of the surface ECG and manually by palpation of the abdominal movement. The freeze was terminated early if the amplitude of the aVF signal decrease by >25% in three consecutive beats or if the diaphragmatic contraction decreased. Results: Phrenic nerve injury documented by a reduction of the signal in aVF was observed in 13 of the 263 patients (5%) during freezes of the right superior pulmonary vein. Reduced diaphragmatic contraction detected by palpation of the abdomen was never observed without previous reduced amplitude in the surface aVF signal and was therefore never the trigger to stop a freeze. In patients with phrenic nerve injury, the mean initial amplitude was 1mV (SD ±0.3mV) and the mean minimal amplitude was 0.3mV (SD ±0.2mV). Mean time to recovery of the aVF amplitude was 160 seconds. Twelve patients (4.6%) showed complete recovery whereas one patient (0.4%) showed only partial recovery, as demonstrated in a sniff test at the end of the procedure. This patient showed no clinical signs of phrenic nerve palsy the following day, and full recovery was demonstrated in a sniff test 3 months later. Conclusion: Monitoring of CMAP using the aVF signal from a standard 12-lead ECG during phrenic nerve stimulation to reduce the incidence of phrenic nerve palsy is safe and feasible. This technique is readily available during every standard ablation without placing additional electrodes and more sensitive than manual palpation. Funding Acknowledgement: Type of funding source: None